Dietary intake of one-carbon metabolism nutrients and DNA methylation in peripheral blood. Issue 3 (8th August 2018) - Chamberlain, James A; Dugué, Pierre-Antoine; Bassett, Julie K; Hodge, Allison M; Brinkman, Maree T; Joo, JiHoon E; Jung, Chol-Hee; Makalic, Enes; Schmidt, Daniel F; Hopper, John L; Buchanan, Daniel D; English, Dallas R; et al.
ABSTRACT: Background: Folate and other one-carbon metabolism nutrients are essential to enable DNA methylation to occur, but the extent to which their dietary intake influences methylation in adulthood is unclear. Objective: We assessed associations between dietary intake of these nutrients and DNA methylation in peripheral blood, overall and at specific genomic locations. Design: We conducted a cross-sectional study using baseline data and samples from 5186 adult participants in the Melbourne Collaborative Cohort Study (MCCS). Nutrient intake was estimated from a food-frequency questionnaire. DNA methylation was measured by using the Illumina Infinium HumanMethylation450 BeadChip array (HM450K). We assessed associations of intakes of folate, riboflavin, vitamins B-6 and B-12, methionine, choline, and betaine with methylation at individual cytosine-guanine dinucleotides (CpGs), and with median (genome-wide) methylation across all CpGs, CpGs in gene bodies, and CpGs in gene promoters. We also assessed associations with methylation at long interspersed nuclear element 1 (LINE-1), satellite 2 (Sat2), and Arthrobacter luteus restriction endonuclease (Alu) repetitive elements for a subset of participants. We used linear mixed regression, adjusting for age, sex, country of birth, smoking, energy intake from food, alcohol intake, Mediterranean diet score, and batch effects to assess log-linear associations with dietary intake of each nutrient. In secondary analyses, we assessed associations with low or high intakes defined by extreme quintiles. Results: No evidence of log-linear association was observed at P  < 10 −7 between the intake of one-carbon metabolism nutrients and methylation at individual CpGs. Low intake of riboflavin was associated with higher methylation at CpG cg21230392 in the first exon of PROM1 ( P  = 5.0 × 10 −8 ). No consistent evidence of association was observed with genome-wide or repetitive element measures of methylation. Conclusion: Our findings suggest that dietary intake of one-carbon metabolism nutrients in adulthood, as measured by a food-frequency questionnaire, has little association with blood DNA methylation. An association with low intake of riboflavin requires replication in independent cohorts. This study was registered at http://www.clinicaltrials.gov as NCT03227003.